Dendritic cell-based vaccine prepared with recombinant Lactococcus lactis enhances antigen cross-presentation and antitumor efficacy through ROS production - Zhang, Tingting; Wei, Xianxian; Li, Yijie; Huang, Shuai; Wu, Yulin; Cai, Shanshan; Aipire, Adila; Li, Jinyao (Frontiers in Immunology, 2023)
Lactococcus lactis (L.L) is safe and can be used as vehicle. In this study, the immunoregulatory effect of L.L on GM-CSF-derived dendritic cell (DC) activation and mechanism were investigated. The immune responses and antigen cross-presentation mechanism of DC-based vaccine prepared with OVA recombinant L.L were explored. L.L significantly promoted DC maturation in a dose-dependent manner, characterized by the upregulated expression of CD40, CD86, TNF-α and IL-12p40, which was partially dependent on TLR2 and downstream MAPK and NF-κB signaling pathways. L.L was internalized into DCs by endocytosis and did not co-localized with lysosome. Moreover, the existence time of L.L in DCs was dependent on reactive oxygen species (ROS) production induced by itself. OVA recombinant L.L enhanced antigen cross-presentation of DCs in an ROS-and proteasome-dependent manner because ROS scavenger and proteasome inhibitor significantly suppressed the presence of MHC I-OVA peptide complex on the surface of DCs. In mouse experiments, L.L increased the migration of DCs to draining lymph node and DC vaccine prepared with OVA recombinant L.L induced strong antigen-specific Th1 and cytotoxic T lymphocyte responses. Importantly, the DC vaccine significantly inhibited B16-OVA tumor growth. Pretreatment with ROS scavenger and proteasome inhibitor abolished the immune responses and antitumor effect of this DC vaccine. This study demonstrated that recombinant L.L as an antigen delivery system prepared DC vaccine could enhance the antigen crosspresentation and antitumor efficacy.